The Analysis of the Demographic Bonus Law on Improving Company Employment Relations - Endeh Suhartini; balvas Imantaka; Nur Fitri Melnia; Putri Romadonna; Cayla; Haikal Ikram Arya Ranggana (Warmadewa Press, 2024)
Every country has a different population. Residents are all people who live in the territory of a country for six months or more and stay temporarily or permanently for different purposes. Population is very important to support the activities of a country, including to improve the performance of the area where the population lives. The existence of the population is also very important in carrying out a company's performance activities, especially in the implementation of labor relations... At the time of the Demographic Bonus, the age of the productive population dominates compared to the age of the unproductive population. The Demographic Bonus, also known as the